(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
In recent decades, disputes over the revocation of the gift agreement have become more frequent in Macedonian courts due to the gross ingratitude of the recipient. This legal standard, which needs to be determined in each case, is interpreted differently by domestic courts, leading to inconsistencies in case law and legal uncertainty. The legislator also contributed to this situation by deleting the social morality as a source of obligatory relations in the general provisions of the Law, replacing it with the good customs that arise from it and with the public order. However, the legislator did not completely erase the morality, leaving it in the regulation of certain principles and issues. Due to this, as well as the fact that the legislator does not explicitly explain what is meant by extreme or great ingratitude, in domestic court practice prevails the view according to which extreme ingratitude means a crime committed against the health, property, freedom, honor and reputation of the donor or his close relative. On the other hand, social and family relationships have changed significantly in recent years, making moral values ​​and responsibilities less respected. In the paper, the authors analyze the legal solutions that regulate the revocation of the gift due to the extreme ingratitude of the recipient and the solutions of the case law, in order to overcome the existing problems related to morality as a source of obligation, for everyone to get the deserved right - ius suum quique tribuere.